2006
DOI: 10.1016/j.nuclphysb.2006.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of the near-extremal NS5-brane

Abstract: We consider the thermodynamics of the near-extremal NS5-brane in type IIA string theory. The central tool we use is to map phases of six-dimensional Kaluza-Klein black holes to phases of near-extremal M5-branes with a transverse circle in eleven-dimensional supergravity. By S-duality these phases correspond to phases of the near-extremal type IIA NS5-brane. One of our main results is that in the canonical ensemble the usual nearextremal NS5-brane background, dual to a uniformly smeared near-extremal M5-brane, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 48 publications
2
18
0
Order By: Relevance
“…One interesting feature in this case is that the system exhibits a Hagedorn behavior, with the localized phase providing a stable phase that extends up to a limiting temperature that lies above the Hagedorn temperature. The same behavior was recently found in the thermodynamics of the nearextremal NS5-brane [41]. More generally, the two-charge system has the interesting aspect that the AdS/CFT correspondence tells us that our deformations of the usual two-charge solution without the presence of the transverse circle should have a counterpart as deformations of the dual two-dimensional CFT.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…One interesting feature in this case is that the system exhibits a Hagedorn behavior, with the localized phase providing a stable phase that extends up to a limiting temperature that lies above the Hagedorn temperature. The same behavior was recently found in the thermodynamics of the nearextremal NS5-brane [41]. More generally, the two-charge system has the interesting aspect that the AdS/CFT correspondence tells us that our deformations of the usual two-charge solution without the presence of the transverse circle should have a counterpart as deformations of the dual two-dimensional CFT.…”
Section: Discussionsupporting
confidence: 78%
“…More generally, it is found that the thermodynamic behavior for the near-extremal two-charge case is completely analogous to that of the near-extremal NS5-brane recently considered in Ref. [41].…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…3) we can use the map (5.23) to make some general observations [58]. For example, the map implies that the (E, r) phase diagram for the near-extremal Dp-branes has the same qualitative form as that in Fig.…”
Section: The Expected T(e) Diagram For D-branes On a Circlementioning
confidence: 99%
“…36 In this section we discuss gauge/gravity duals in which the gravity side exhibits a Gregory-Laflamme instability. The presence of this classical gravitational instability in the bulk has important consequences for the gauge theory on the boundary, which we review following [56,57,155,66,58]. Focusing on a set of examples that are closely connected to the material of this review we will consider first D-branes on a circle, where the relevant gauge theory is super-Yang-Mills theory on a circle.…”
Section: Holographic Implicationsmentioning
confidence: 99%